INVESTIGATION OF A LIMESTONE PILLAR FAILURE PART 2: STRESS HISTORY AND APPLICATION OF FRACTURE MECHANICS APPROACH - Alber M.; Heiland J. (My University, 2001)
Observed pillar failure could not be explained by comparing pillar strength with stresses on the pillar induced by mining activities. Instead, the effects of the combined stress history of strata and pillar on the deformational response of rock mass and rock were assessed. Application of the principles of fracture mechanics, i.e., extension strain and strain energy release rate criteria gave a reasonable explanation for the observed pillar behavior. The derivation of the required fracture mechanics parameters from laboratory tests is described, and the necessity of an interdisciplinary approach to rock engineering, i.e., the use of historical geology, engineering geology, mining engineering and rock mechanics, is mandated.